Pengaruh Pemberian Kombinasi Takaran Bokashi Pupuk Kandang Kambing dan NPK Terhadap Pertumbuhan Dan Hasil Jagung Manis (Zea mays L. Saccharata) - Olifia; Dewirman Prima Putra; Bustari Badal (Fakultas Pertanian, Universitas Ekasakti, 2022)
The research was conducted in Kandih Raya, Kampung Olo, Nanggalo District, Padang City, West Sumatra. The experiment was carried out from January to April 2020. The aim of this study was to obtain the best combination dose of bokashi goat manure and NPK 16:16:16 on the growth and yield of sweet corn. The design used was a randomized block design (RBD) with 7 treatments and 3 groups. The treatments were various combinations of dosage of bokashi goat manure and NPK, namely: A = 0 tonnes / ha bokashi goat manure and 300 kg NPK 16:16:16 B = 10 tonnes / ha bokashi goat manure and 250 kg NPK 16:16 : 16 C = 10 tonnes / ha bokashi goat manure and 300 kg NPK 16:16:16 D = 15 tonnes / ha bokashi goat manure and 250 kg NPK 16:16:16 E = 15 tonnes / ha bokashi goat manure and 300 kg NPK 16:16:16 F = 20 tons / ha bokashi goat manure and 250 kg NPK 16:16:16 G = 20 tons / ha bokashi goat manure and 300 kg NPK 16:16:16. The use of the combined dose of bokashi goat manure and NPK gave no significant effect on: stem diameter, harvest age, ear length and diameter and ear weight without husks per plant, showing significant differences on: flowering age, and ear weight with weight per plant. and showed significantly different effects on: plant height, longest leaf length, widest leaf width, number of leaves and ear weight without husks per plot. The combination of dosage combination of bokashi goat manure at 15 ton / ha and 300 kg / ha NPK 16:16:16 was the best treatment for the growth and yield of sweet corn plants.